Kajian Pemanenan Air Hujan Skala Individual Untuk Pemenuhan Air Baku Wilayah Pesisir Wilayah Kajian : Desa Tanah Merah, Kecamatan Tanah Merah, Kabupaten Indragiri Hilir - Triliani, Ana Aulia; Suprayogi, Imam; Sasmita, Aryo (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Indragiri Hilir Regency is a condition of the area which is dominated by salt water, the water quality is very inadequate in terms of quantitative and qualitative hydrology due to swamp environmental conditions. Therefore the need for other alternatives to meet raw water needs by utilizing Rainwater Harvesting technology. In this study conducted the study in Tanah Merah Village, Tanah Merah District, Indragiri Hilir Regency. To find out the large contribution of rainwater harvesting, design designs, and budget plans that are carried out calculation and analysis of data. Supported by the Raincycle Standard v2.0 program based on the falling raindrops (roof's drip) which is the catchment area and water requirements based on the number of family members of each type of house. And the results obtained after the analysis of data for rainwater catchment areas, namely with an area of 208 m², 156 m², and 126 m², the percentage of rainwater donations fulfilled by 3 tanks is 82% with a planned budget of Rp 14,358,000.00 while for the rainwater catchment area, which is 80 m² in size, and 49 m² of the percentage of rainwater donation that is fulfilled by 2 tanks is 72% with a budget plan that is Rp. 10,332,000.00. And in terms of quality parameters that exceed the quality standard, namely detergent, to reduce the levels, namely by filtering with filters from media activated carbon, sand, and silica. Keywords: Rainwater Harvesting, Indragiri Hilir Regency, Raw Water